The effect of captopril on membrane bound enzymes in ischemia–reperfusion injury - (:unkn) unknown (My University, 2000)
There is substantial evidence that Na+ K+/Mg2+ ATPase and Ca2+/Mg2+ ATPase enzymes would effect the membrane integrity. Forty guinea pig (n = 10 in each group) hearts were studied in an isolated Krebs—Henseleit solution perfused Langendorff cardiac model. The first group was utilized as the control group. Group 2 hearts were arrested with captopril (200 μmol/l) added St Thomas Hospital Cardioplegic Solution (STHCS). Group 3 animals were pretreated with oral captopril (0.3 mg/kg/twice a day) for 10 days and then arrested with STHCS. Group 4 hearts were again pretreated with oral captopril (0.3 mg/kg/twice a day for 10 days) arrested with STHCS and reperfused with captopril added Krebs—Henseleit solution (200 μmoi/l). Hearts were subjected to normothermic global ischemia for 90 min and than were reperfused at 37°C. When the treated groups were compared with control, best results were achived by group 4. The Na+ K+ and Ca2+/Mg2+ ATPase levels increased from 466.38 ± 5.99 to 564.13 ± 7.77 and 884.69 ± 9.13 to 1254.29 ± 5.75 nmol Pi/mg/prot/h respectively (P < 0.05). These results suggest that captopril protects the membrane integrity and thus played a role at the recovery of depressed membrane bound Na+ K+ /Mg2+ ATPase and Ca2+/Mg2+ ATPase activity and also in ischemia—reperfusion injury. © 2000, The International Society for Cardiovascular Surgery. All rights reserved.
Keywords: Ca2+/Mg2+ ATPase; captopril; cardioplegia; ischemia—reperfusion injury; myocardial protection; Na+ K+/Mg2+ ATPase